2018
DOI: 10.2478/hukin-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inspiratory Muscle Training on Performance of Handball Athletes

Abstract: Inspiratory muscle training (IMT) is a strategy that has been used to improve performance in different sports modalities. This study investigated the effects of an IMT program on respiratory muscle strength and resistance as well as aerobic physical performance (PP) of handball athletes. Nineteen 20 ± 3 year-old male athletes were allocated into an experimental (EG, n = 10) or a placebo group (PG, n = 9). Their respiratory muscle strength was evaluated by measuring the maximum inspiratory and expiratory pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 30 publications
2
44
0
1
Order By: Relevance
“…Among the first, in the article by Najafi et al [37], increases of 8.9% were achieved with a moderate ES of 0.77 in experimental group 1 (55% MIP), and 8.1% with a moderate ES of 0.78 in experimental group 2 (40% MIP); however, in the article by Romer et al [58], the increase was approximately 7% with a moderate ES of 0.25. Both studies are in line with other studies conducted with semi-professional handball players [65] and football players [2], which showed performance improvements.…”
Section: Sports Practiced and Sports Levelsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the first, in the article by Najafi et al [37], increases of 8.9% were achieved with a moderate ES of 0.77 in experimental group 1 (55% MIP), and 8.1% with a moderate ES of 0.78 in experimental group 2 (40% MIP); however, in the article by Romer et al [58], the increase was approximately 7% with a moderate ES of 0.25. Both studies are in line with other studies conducted with semi-professional handball players [65] and football players [2], which showed performance improvements.…”
Section: Sports Practiced and Sports Levelsupporting
confidence: 92%
“…It is important to note that many of the other articles did not assess MEP, but for those that did, they did not observe any significant increases. It would be interesting to determine whether the work of the inspiratory muscles can favor the work of the expiratory ones, as this seems to be indicated in an article with semi-professional handball players where the MIP increased by 54% and the MEP by 23% [65]. Only one study used PowerLung, a device that presents a load on both the inspiratory and expiratory phases [59]; however, since it did not provide MEP data, a comparison could not be made.…”
Section: Sports Practiced and Sports Levelmentioning
confidence: 99%
“…Studies related to the national teams of two of the world’s major countries in this sport – Norway and Denmark – have confirmed that experience in the Norwegian national youth and junior teams is associated with the number of international matches played in the senior category ( Bjorndal et al, 2018 ), and that the relative age effect is apparent in Danish national men’s teams at these younger levels ( Wrang et al, 2018 ). Regarding the training programs, it has been found that programs targeted at the inspiratory muscles not only improve these muscles in particular, but also contribute to enhancing aerobic performance ( Hartz et al, 2018 ) and postural stability exercises implementing the biofeedback method on stabilo and dynamometric platforms are practical and justifiable in junior goalkeepers ( Wilczyński, 2018 ). Pre-season conditioning programs that include working on hamstring and quadriceps muscles are needed to reduce the risk of injury ( Spieszny and Zubik, 2018 ).…”
mentioning
confidence: 99%
“…The study will be conducted using the POWERbreath ® mechanical loading device (Medic, London, United Kingdom). Although a training proposal with this equipment has already been described in the literature in athletes [24], outpatients [25] and patients with chronic obstructive pulmonary disease [26], to the best of our knowledge, no study has analysed early IMT using this device in mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 99%